Individual and collective protective responses during the early phase of the COVID-19 pandemic in 10 different countries: Results from the EUCLID online survey. (September 2022) - Koller, Julia E.; Villinger, Karoline; Lages, Nadine C.; Absetz, Pilvikki; Bamert, Melanie; Branquinho, Cátia; Chaves-Avilés, Lourdes; Dimitropoulou, Panagiota; Fernández-Fernández, Ana Lucía; Gaspar de Matos, Margarida; Griskevica, Inguna; Gutiérrez-Doña, Benicio; et al.
Highlights: Behavioral changes and governmental strategies are needed to address COVID-19. Protective behaviors and support for measures are often studied separately. However, these individual and collective pathways are cross-amplifying. Research should address connections between individual and collective pathways. Abstract: Background: In times of unprecedented infectious disease threats, it is essential to understand how to increase individual protective behaviors and support for collective measures. The present study therefore examines factors associated with individual and collective pathways. Methods: Data was collected through an online survey from 4483 participants (70.8% female, M = 41.2 years) across 10 countries from April 15, 2020 to June 2, 2020 as part of the "EUCLID" project (https://euclid.dbvis.de ). Structural equation modeling was used to examine individual and collective pathways across and within countries. Results: Overall, the adoption of individual protective behaviors and support for collective measures were high. Risk perception on the individual level and perceived effectiveness at the collective level were positively associated with both individual protective behaviors and support for collective measures. Furthermore, the model explained considerable variance in individual (40.7%) and collective protective behaviors (40.8%) and was largely replicated across countries. Conclusions: The study extends previous research by demonstrating that individual risk perception and perceived effectiveness of collective measures jointly affect individual protective health behaviors and support for collective measures. These findings highlight the need to jointly consider a variety of behavioral actions against infectious disease threats, acknowledging interactions between individual and collective pathways. Graphical abstract: This is special type of abstract that is so short and could be inserted after main abstract of article, as a blurb or inserted as annotations into a Table of contents Image, graphical abstract